Safety of lung stereotactic ablative radiotherapy for the functioning of cardiac implantable electronic devices. (March 2021) - Levis, Mario; Andreis, Alessandro; Badellino, Serena; Budano, Carlo; Caivano, Donatella; Cerrato, Marzia; Orlandi, Erika; Bissolino, Arianna; Angelico, Gloria; Cavallin, Chiara; Giglioli, Francesca R.; De Ferrari, Gaetano M.; et al.
Highlights: The number of patients with a CIED requiring a course of RT in increasing remarkably. We report the first in-vivo report of thoracic SABR in patients with a CIED. No CIEDs-dysfunctions were observed, keeping the max dose <2 Gy to the devices. Thoracic SABR can be safely administered to CIED-bearing patients. Abstract: Background and purpose: The prevalence of patients with a cardiac implantable device (CIED) developing cancer and requiring a course of radiotherapy (RT) is increasing remarkably. Previously published reports agree that standard and conventionally fractionated RT is usually safe for CIEDs, but no "in-vivo" reports are available on the potential effects of thoracic stereotactic ablative radiotherapy (SABR) regimens to CIEDs functioning. The purpose of our study is therefore to evaluate the effects of SABR on CIEDs (pacemakers [PM] or implantable cardiac defibrillators [ICD]) in a cohort of patients affected by primary or metastatic lung lesions. Materials and methods: We retrospectively collected all CIED-bearing patients undergoing SABR between 2007 and 2019 at our Institution. All CIEDs were interrogated before and after the SABR course to check for any malfunction. Prescription dose, beam energy and maximum dose (Dmax) to CIEDs were retrieved for each patient. Electrical records of the CIEDs were reviewed by the medical records. Results: Thirty-four consecutive patients (24 with a PM and 10 with an ICD), who underwent 38 separate SABR courses, were included in the study. Eight patients (24%) were PM-dependent. Prescription dose of SABR ranged 26–60 Gy in 1–8 fractions, with a photon energy ranging 6-to-10 MV (76.3% and 23.7%, respectively) and a median Dmax to CIEDs of 0.17 Gy (range 0.04–1.97 Gy). Electrical parameters were stable in post-treatment device programming visits and no transient or persistent alteration of the CIED function was recorded in any patient. No inappropriate interventions were recorded in the 10 ICD-bearing patients during the treatment fractions. Conclusions: Thoracic SABR proved to be safe for CIEDs when the dose is kept <2 Gy and the beam energy is ≤10 MV, irrespective of the pacing-dependency and of the CIED type.